In-house isolation protocol from human serum samples demonstrates the circulating of a broad diversity of Leptospira serogroups in Costa Rica - Diana Chinchilla; Inés Sánchez; Diego Montero; Mathieu Picardeau; Ricardo Gutiérrez (Scientific Reports)
Abstract The isolation of pathogenic Leptospira is fundamental for a comprehensive characterization of circulating strains in endemic regions. Unfortunately, culture methods of Leptospira spp. are laborious and challenging. Here, we present a method for the isolation of these pathogenic bacteria from non-fresh serum samples, previously stored at 4–8 °C for several days. Briefly, 730 serum samples collected from leptospirosis-suspected patients (presenting acute signs) were screened for Leptospira DNA by real-time PCR. Thirty-one PCR-positive sera were then assessed for Leptospira isolation on specialized media for up to 6 months. Using this methodology, 11 Leptospira isolates were obtained, resulting in an isolation rate of 35.4% (11/31). Through whole-genome analysis, ten strains were identified as Leptospira santarosai and one strain as Leptospira borgpertersenii. The isolates were classified into six different serogroups, namely Hebdomadis, Shermani, Tarassovi, Pyrogenes, Ballum, and Grippotyphosa, demonstrating a wide diversity of Leptospira strains circulating in Costa Rica. This study reveals that serum is a suitable sample for Leptospira isolation in patients with positive PCR results, even after maintenance at cold conditions, promoting the use of serum for Leptospira isolation in reference laboratories around the world.